An Improved One-Pot Procedure for Preparation Of N,N -Diethyl-m-Toluamide from m-Toluic Acid - Thinh Pham Duc; Thu Nguyen Van; Phuong Bui Thu; Chau Phan Dinh; Duc Viet Le; Duong Vu Binh (Revista Cubana de Medicina Militar)
Introduction: Recent statistics have shown that there are hundreds of diseases caused by insects that have a significant impact on human health and they are often fatal. Mosquitoes cause about 10 diseases, most notably malaria, dengue fever and zika fever. N,N-diethyl-m-toluamide (1, DEET) or N,N-diethyl-m-methylbenzamide was globally approved under brand names m-Dephene, Detamide, Flypel as one of the most prominent agents for preparation of insect repellants. Objectives: To present an enhanced method for synthesis of N,N'-diethyl- m-toluamide which can be introduced to industrial scale. Method: The input materials: m-toluic acid has been activated with thionyl chloride to create the intermediate product, m-toluoyl chloride. This product then was reacted with diethylamine in order to produce DEET. This method has been improved the factors affecting the synthesis of DEET. Results: DEET was successfully synthesized using well known materials with high efficiency and purity. During research all the by-products and waste materials in the reaction are highly water-soluble, therefore the final product was obtained at pharmaceutical requirement without further purification. The analytical data has shown that DEET was collected at a very high yield in the range of 96-98%, purity (HPLC): 95.5-97.6%. The structure of DEET was determined by model spectroscopies MS, and NMR. Conclusions: An improved procedure for the synthesis of N,N-diethyl-m -toluamide (DEET) or N,N-diethyl-m-methylbenzamide is established where the use of all reagents was optimized in suitable amount to apply in industrial production.